G35 A Review of the Outcome of a Cohort of Infants Born with Trisomy 18. (4th June 2013) - Jalloh, S; Baker, K; Damodaran, S; Roy, R; Kelsall, W
Abstract : Trisomy 18 (T18), Edward's syndrome, is a rare condition with a prevalence of 0.1/1000 livebirths in the UK. 1 The majority of these infants do not survive the neonatal period with up to 10% surviving for a year 2 . Clinicians are faced with difficult discussions regarding outcome. This study stems from questions posed by parents of a baby girl who died at home aged 22 months. The study was designed to address the parents' questions: 1.What is the likelihood of a baby being born with T18 with no identified antenatal risk factors? 2.What is the prognosis for a baby born with T18? 3.What support should families receive following a diagnosis of T18? Method: Retrospective study of all karyotype confirmed postnatal diagnoses of T18, born between 2000 and 2010 at hospitals within a perinatal network. Patients were identified from genetic databases. Information was extracted from paediatric case-notes to a pre-designed audit sheet. Results: Over 11years, 19 live born cases were identified. Information is available for 18. Nine cases (50%) were suspected antenatally but karyotyping declined until after birth. Nine cases (50%) were not suspected before birth. The median gestation was 38 weeks with range of associated anomalies; cardiac defects being the commonest. 4 babies died before discharge and all babies discharged from hospital had a named paediatric consultant. Survival was 94% at one week, 72% at one month, 39% at 3 months, 22% at 6 months and 11% at one year of age. Community nursing and hospice support was provided for 12 (66%) babies. Clinical genetics input was documented for 16 families; 6 before and 10 after discharge. Evidence of end-of-life -planning was poorly documented in the case notes. Conclusions: Half of the babies in this cohort were not suspected antenatally. Overall survival rate was 10% at one year consistent with previous studies but medium term survival was higher than other published studies. Better documentation of end of life care is required.